Analysis of the factors affecting the students' choice of librarianship as a career - Espiritu, Maria Ana Corazon A. (2012)
There is a continuous demand of librarians in every aspect of society: national, foreign, medical, law and information technology. Sadly, this demand cannot be addressed because of the very low supply being produced. Library schools and institutions cannot match up the work force with a few Library and Information Science graduates every year. This study aims to know some of the factors that affect students' choice of a career. The main objective of this study was to analyze the factors that affect the student's choice of librarianship as a career.